Education of the impellent-plastic expressiveness at a stage of specialized base preparation in art gymnastics. - Kravchuk T.N; Sanzharova N.N; Golenkova J.V; Litovko T.V (Kharkov National Pedagogical University, 2010)
In the given article is proved and opened the technique of education of the impellent-plastic expressiveness at a stage of specialized base preparation in art gymnastics. Criteria and modern requirements to the impellent-plastic expressiveness of gymnasts are analyzed. Its basic components are defined: musical-rhythmic preparation; mastering by skills of expressive movement; choreographic preparation; studying of elements of national and ball dances.